1990
DOI: 10.1111/j.1432-1033.1990.tb15384.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and properties of two oxidoreductases catalyzing the enantioselective reduction of diacetyl and other diketones from baker's yeast

Abstract: The NADPH-linked diacetyl reductase system from the cytosolic fraction of Saccharomyces cerevisiae has been resolved into two oxidoreductases catalyzing irreversibly the enantioselective reduction of diacetyl (2,3-butanedione) to (9-and (R)-acetoin (3-hydroxy-2-butanone) [so-called (S)-and (R)-diacetyl reductases] (EC 1.1.1.5) which have been isolated to apparent electrophoretical purity.The clean-up procedures comprising streptomycin sulfate treatment, Sephadex G-25 filtration, DEAESepharose CL-6B column chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…Lanes 1, 2, 5, 6, 9, and 10 show the expression levels of Bdh1p-6His in the cell extracts of strains WCG4-11/22a (lanes 1 and 2), FY834 (lanes 5 and 6), and FY834 bdh1⌬ (lanes 9 and 10). Lanes 3,4,7,8,11,and 12 show the expression of Bdh2p-6His in the cell extracts of strains WCG4-11/22a (lanes 3 and 4), FY834 (lanes 7 and 8), and FY834 bdh1⌬ (lanes 11 and 12). effect of the oxygen supply during yeast fermentation on the formation of 2,3-butanediol through acetoin was previously observed (15).…”
Section: Discussionmentioning
confidence: 99%
“…Lanes 1, 2, 5, 6, 9, and 10 show the expression levels of Bdh1p-6His in the cell extracts of strains WCG4-11/22a (lanes 1 and 2), FY834 (lanes 5 and 6), and FY834 bdh1⌬ (lanes 9 and 10). Lanes 3,4,7,8,11,and 12 show the expression of Bdh2p-6His in the cell extracts of strains WCG4-11/22a (lanes 3 and 4), FY834 (lanes 7 and 8), and FY834 bdh1⌬ (lanes 11 and 12). effect of the oxygen supply during yeast fermentation on the formation of 2,3-butanediol through acetoin was previously observed (15).…”
Section: Discussionmentioning
confidence: 99%
“…It was shown by Hardwick et al 7 that alcohol dehydrogenase (ADH 1; EC 1.1.1.1) will reduce diacetyl and pentanedione, albeit rather less efficiently than it deals with acetaldehyde, but it was also shown that yeast contains other enzymes capable of reducing the VDKs. Others have reported specific diacetyl reductases (EC 1.1.1.5) in yeast 8,14,16 . Attention has been drawn 10 to the challenges involved in unraveling the literature on the diversity of oxidoreductases in an organism such as yeast.…”
Section: Introductionmentioning
confidence: 99%
“…The ADH from strain GK1 did not oxidize 2,3 butanediol or acetoin (Table 2), in common with two oxidoreductases from S. cerevisiae (Heidlas and Tressl 1990).…”
Section: Oxidation Of Alcoholsmentioning
confidence: 99%
“…A wide variety of bacteria (Seitz et al 1963 ;Ui et al 1987 ;Hummel et al 1989 ;Gibson et al 1991 ;Blomquist et al 1993) and yeasts (Louis-Eugène et al 1988 ;Verduyn et al 1988 ;Legeay et al 1989 ;Heidlas and Tressl 1990 ;Hang and Woodams 1993 ;Olguin-Castillo et al 1994) display a diacetyl reductase. Chicken liver has also been described as a source of this enzyme (Gibson et al 1991).…”
Section: Introductionmentioning
confidence: 99%